Sejarah Kurikulum 2013 Sebagai Implementasi Sikap Spritual Anak Didik - Isroiyah, Isroiyah (JOIES (Journal of Islamic Education Studies), 2021)
The curriculum as a planned program to combine the scope, sequence, interpretation, balance of subject matter teaching techniques into a series of teaching activities. In the 2013 curriculum program, the Rencana Pembangunan Jangka Menengah Nasional (RPJMN) for 2010-2014 mandates the need for a realignment of the current curriculum. This study wants to explore the history of the 2013 curriculum in the context of spiritual skills. To answer this, the researchers conducted a literary research. This study found that in essence the factors behind the changes in the 2013 curriculum were: 1) The challenges of the times and the demands of maintaining morals. 2) Maximum efforts to build a whole person 3) Efforts to maximize the achievement of educational goals 4) Cultural roots and efforts to knit Indonesia 5) Respond to internal challenges 6) Respond to external challenges 7) Introduction to curriculum governance and material arrangement. Spiritual implementation in the 2013 curriculum is carried out by means of self-awareness to learn from the scientific stages of spiritual bayani, spiritual irfani and spiritual burhani. The study of spiritual bayani is a study of the spirituality of the Koran and hadith based on logical thinking or a rational approach.